Evaluate The Application Of The 4 Principles Correctly On Fertilizing Aktivities For Empty Plam Oil - Sri Ngapiyatun; Robet; Puspita; Wartomo; Humairo Aziza; Rusli Anwar; Arief Rahman (Politeknik Pertanian Negeri Samarinda, 2025)
This research is based on the soil conditions at PT. Cipta Davia Mandiri which tend to be rocky and sandy so that fertilization is needed. One of the right fertilizers is empty bunch fertilizer because it can improve soil structure, soil texture, aeration and increase soil absorption capacity to water. This study aims to determine the evaluation of the application of the 4 right principles in empty bunch fertilization activities referring to the 4 right and to determine the achievement of the target results of empty bunch fertilization work based on the 4 right principles. The method used is the Quantitative method using saturated sampling (census sampling) where all populations are used as samples. In this study, the sample used was 10 employees because the fertilization employees only numbered 10 people. Fertilization activities were carried out in block 227A division 08. Based on the results of the research on the 4 Right Principles in the application of empty fruit bunch fertilizer, all of them have met the accuracy requirements, both the right type with an average value of 100%, the right dose with an average of 91.48%, the right time with an average of 100%, and the right method with an average of 95.39% and the achievement of the work target of empty fruit bunch fertilization employees on average reached the work target of up to 31 trees/HK from the target of 32 trees/HK with a percentage value of 96.87%.